2012
DOI: 10.4103/0970-1591.105775
|View full text |Cite
|
Sign up to set email alerts
|

Complete penoscrotal transposition: A three-stage procedure

Abstract: Complete penoscrotal transposition (CPST) with an intact scrotum is a rare anomaly in which the scrotum is located cephalic to the penis. It is the most severe degree of malformation of a spectrum of abnormalities in scrotal development. There are few cases reported in the literature, and there are few descriptions of the technique for correction and results. We describe a new case of CPST and its sequential correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…PST is a very rare clinical situation in which the scrotum is located anterior and superior to the penis and a severe degree of PST, as in our case, with hypospadias and normal scrotum have been infrequently reported in medical literature ( 1 , 3 , 4 ) . During normal human maturation, scrotal swellings move inferomedially during the 9 th -11 th week, and fuse in the midline caudal to the penis by the 12 th week of gestation ( 4 ) .…”
Section: Dear Editormentioning
confidence: 59%
“…PST is a very rare clinical situation in which the scrotum is located anterior and superior to the penis and a severe degree of PST, as in our case, with hypospadias and normal scrotum have been infrequently reported in medical literature ( 1 , 3 , 4 ) . During normal human maturation, scrotal swellings move inferomedially during the 9 th -11 th week, and fuse in the midline caudal to the penis by the 12 th week of gestation ( 4 ) .…”
Section: Dear Editormentioning
confidence: 59%
“…Usually an operative correction is offered at 12-18 months of age [5]. Somoza et al had successfully demonstrated a 3-staged correction, 1st stage being done at 18 months of life after topical Testosterone application [1]. Our patient has been discharged with a plan to do a staged repair at around the same age.…”
mentioning
confidence: 69%
“…A pre-penile scrotum or a complete penoscrotal transposition [CPST] is a rare congenital anomaly where the phallus lies between the scrotum and anus. Less than 20 cases of CPST with intact scrotum are reported in the literature [1]. Most of the cases are sporadic.…”
mentioning
confidence: 99%
“…As an isolated abnormality, there are less than 20 cases described in the literature. 3 Ectopic scrotum is the rarest anomaly of this gland. 4 In the patient herein reported, the ectopic penis and scrotum represented an association not described in the literature yet.…”
Section: Discussionmentioning
confidence: 99%